The effect of third zone intensity training on the speed-strength of the arms certain biochemical indicators and the completion time of a 50-meter freestyle swim - Kadhim, Farqad (Journal of Physical Education, 2025)
The research aimed to prepare and apply third zone intensity training for 50-meter freestyle swimmers, examining its impact on the speed strength of the arms, some biochemical indicators, and the completion time for 50 meters freestyle. The researcher hypothesized that there would be statistically significant differences between pre- and post-test results for the experimental and control groups in arm speed strength, biochemical indicators, and completion time. The experimental method involved a design with both experimental and control groups, consisting of 11 swimmers from the Army Club participating in the 2024/2025 sports season, selected intentionally with a 100% comprehensive approach. After determining the tests and preparing the training, the experimental group underwent two training sessions per week for 10 weeks. Results were analyzed using SPSS. Conclusions and recommendations indicated that applying third zone intensity training during the specific preparation period helps develop arm speed strength for 50-meter freestyle swimmers, outperforming peers who train without it. It also aids in regulating blood salts (calcium, potassium, sodium) among these swimmers, again outperforming their peers. Additionally, it improves completion time for 50 meters freestyle for those who train with it, surpassing those who do not. It is crucial to avoid excessive resistance increases when training arm speed strength with third zone intensity training for 50-meter freestyle swimmers. Furthermore, monitoring biochemical indicators of blood salts is essential for assessing swimmer health and cellular regulation during third zone intensity training.